THE INFLUENCE OF DEVELOPING HUMAN CAPITAL MANAGEMENT TOWARD COMPANY PERFORMANCE (THE EVIDENCE FROM DEVELOPER COMPANIES IN SOUTH SULAWESI INDONESIA) - Hidayat, Muhammad; Latief, Fitriani (Program Pascasarjana STIE Amkop Makassar, 2018)
Human capital is the key factor to drive a company in achieving its vision and mission. Therefore, developing human capital management aims to achieve the company's human capital quality, it is one of the most important company’s strategies today. This study is intended to determine the influence of human capital management development toward the company performance, to answer this question the five important factors in human capital management, namely individual capabilities, individual motivation, leadership, organizational climate and work group effectiveness, they are analyzed to determine their effects on employee performance and company performance on four developer companies in South Sulawesi Indonesia. This study proved that the organizational climate has a direct effect on employee and company performance. Work group effectiveness directly affects employee and company performance. Individual capability, individual motivation, and leadership have a direct effect on employee performance. Then the employee performance directly affects the company performance. Keywords: Development, Human Capital Management, Corporate Performance